Comparative political theory an introduction - Dallmayr, Fred R. (Palgrave Macmillan, 2010)
Political theory has been traditionally confined to the history of Western political thought from Aristotle to Nietzsche, but this limitation is not tenable in a global age. This text focuses on Islamic, Indian and Far Eastern civilizations, offering readings of classical teachings and contemporary theoretical developments.